Quasi-solid polymer electrolyte and preparation method thereof
By introducing dynamic covalent disulfide bonds and hydrogen bonds into quasi-solid polymer electrolytes and combining them with post-immersion method, the problem of difficult to take into account both mechanical properties and ionic conductivity is solved, and excellent electrochemical performance in lithium-ion batteries is achieved. Self-healing performance improves the stability and application of the battery.
Patent Information
- Application Number
- CN202411243102.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-13
AI Technical Summary
The existing quasi-solid polymer electrolytes are difficult to take into account excellent mechanical properties and high ionic conductivity, resulting in safety hazards in lithium-ion batteries.
A polyurethane urea system was designed, by introducing dynamic covalent disulfide bonds and hydrogen bonds, and adding lithium salts, plasticizers and fluorovinyl carbonate after combination, controlling the immersion time and substance ratio, forming excellent mechanical properties. and ionic conductivity quasi-solid polymer electrolyte.
A quasi-solid polymer electrolyte that balances mechanical properties and ionic conductivity in lithium-ion batteries has excellent electrochemical properties and self-healing properties, and improves the cycle stability and application of the battery.
Smart Images

Figure CN119133590A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion batteries, and in particular relates to a quasi-solid polymer electrolyte and a preparation method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Lithium-ion batteries have been used in various aspects of life, such as electric vehicles, portable devices, and power generation equipment, and are an indispensable part of people's daily lives. However, due to the shortcomings of liquid lithium-ion batteries such as easy leakage and lithium dendrite growth, there are great safety risks in their use in daily life. Solid polymer electrolytes (SPEs) with excellent mechanical strength and processability are considered to be the first choice to replace traditional liquid organic electrolytes. Among them, solid polymer electrolytes (SPEs) include two types, pure solid polymer electrolytes and quasi-solid polymer electrolytes. Pure solid polymer electrolytes refer to those without liquid, only solid, while quasi-solid polymer electrolytes refer to those with both solid and a certain amount of liquid.
[0004] As we all know, the currently desired SPEs need to have excellent mechanical properties and good ionic conductivity. Excellent mechanical properties can provide SPEs with a strong skeleton, microscopic ion channels and excellent anti-dendritic properties. Similarly, ionic conductivity is also an important indicator for measuring the electrochemical performance of SPEs. Ionic conductivity is a key factor in determining the internal resistance and rate performance of batteries. SPEs with high ionic conductivity can transmit current more efficiently. For quasi-solid polymer electrolytes, the ionic conductivity of quasi-solid polymer electrolytes can be improved by increasing the content of plasticizers and lithium salts in the electrolyte. At the same time, the plasticizing effect of plasticizers and the complexing effect of lithium salts further reduce the mechanical properties of the electrolyte. At present, many experiments have also shown that it is difficult to balance the ionic conductivity and mechanical properties of quasi-solid polymer electrolytes. Summary of the invention
[0005] In order to solve the problem of balancing ionic conductivity and mechanical properties in the prior art, the present invention provides a quasi-solid polymer electrolyte and a preparation method thereof, wherein a polyurethane urea system is innovatively designed and a simple method is used to solve this problem. The polyurethane urea is designed to be rich in hydrogen bonds and introduce dynamic covalent disulfide bonds, a skeleton network is formed by cross-linking, lithium salts and plasticizers are added to the polymer by post-immersion method, and the immersion time is controlled. The key is to add fluoroethylene carbonate (FEC) with a volume fraction of about 3-8% as a stabilizer for the electrolyte, and control the content of lithium salts and plasticizers in the polymer electrolyte.
[0006] In order to solve the above technical problems, the technical solution of the present invention is:
[0007] In a first aspect, the present invention provides a quasi-solid polymer electrolyte, comprising: a polyurethane urea elastomer and a soaking solution; the soaking solution comprises a lithium salt, a plasticizer and fluoroethylene carbonate.
[0008] Wherein, the fluoroethylene carbonate is a stabilizer in the electrolyte.
[0009] In some embodiments, the lithium salt is selected from one of lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluoromethanesulfonyl)imide, lithium dicyanotriazole, lithium tetrafluoroborate and lithium bis(oxalatoborate); preferably, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide.
[0010] In some embodiments, the plasticizer is selected from tetraethylene glycol dimethyl ether and succinonitrile; preferably one; preferably, the plasticizer is tetraethylene glycol dimethyl ether.
[0011] In some embodiments, the volume fraction of the fluoroethylene carbonate (in the total volume fraction) is 3-8%; preferably, the volume fraction of the fluoroethylene carbonate is 5%.
[0012] In some embodiments, the mass ratio of lithium salt to plasticizer is (1-5):(5-10), preferably (1-2):(6-7), and further preferably 2:7.
[0013] In some embodiments, the mass ratio of the lithium salt material, the plasticizer and the fluoroethylene carbonate is (1-5):(5-10):1, preferably 4:14:1.
[0014] In a second aspect, the present invention provides a method for preparing a quasi-solid polymer electrolyte, comprising:
[0015] preparing a polyurethane urea elastomer containing dynamic covalent bonds and processing it into a polyurethane urea elastomer tablet;
[0016] The plasticizer and the lithium salt are mixed to prepare a lithium salt solution, and fluoroethylene carbonate is added thereto to obtain a soaking solution;
[0017] The polyurethane urea elastomer pressed sheet is completely immersed in the soaking solution for a certain period of time, and the surface is wiped after being taken out to obtain a quasi-solid polymer electrolyte.
[0018] In some embodiments, the preparation method of the polyurethane urea elastomer is to add a mixture of an organic solvent, dibutyl tin dilaurate and hexamethylene diisocyanate to completely melted polyethylene glycol and heat it, then add a chain extender solution in sequence to carry out a prepolymerization reaction, add a crosslinker solution to carry out a crosslinking reaction, and finally perform subsequent treatment to obtain a polyurethane urea elastomer containing dynamic covalent bonds.
[0019] The dynamic covalent bonds are disulfide bonds. The introduction of dynamic covalent bonds gives the quasi-solid electrolyte excellent self-healing properties. Dynamic covalent bonds can be broken and reorganized under external stimuli. For example, these bonds can be broken under appropriate conditions at high temperatures or external impacts, and re-formed under environmental conditions or external stimuli.
[0020] In some embodiments, in the mixed solution, the ratio of hexamethylene diisocyanate, organic solvent and dibutyltin dilaurate is (0.2-0.4):(5-15):(15-25), g:mL:μL.
[0021] Furthermore, in the mixed solution, the organic solvent is DMF or DMSO.
[0022] Further, the mixed solution is added into completely melted polyethylene glycol, and heated at 60° C.-80° C. for 1-2 h; preferably, heated at 70° C. for 1.5 h.
[0023] Furthermore, the mass fraction of the polyethylene glycol is 1000-3000 g·mol -1 .
[0024] In some embodiments, the chain extender solution includes a chain extender and an organic solvent for dissolving the chain extender. The chain extender is 4,4'-diaminodiphenyl disulfide; and the organic solvent is DMF or DMSO.
[0025] Furthermore, the mass ratio of the chain extender to the organic solvent is 1:(200-240), preferably 1:240; the molar ratio of the chain extender to polyethylene glycol is 1:(1-4), preferably 1:2.
[0026] Furthermore, in the prepolymerization reaction, the heating condition is heating at 60°C-80°C for 1-3h; preferably, heating at 70°C for 2h.
[0027] In some embodiments, the crosslinker solution includes a crosslinker and an organic solvent that dissolves the crosslinker; the crosslinker is trimethylolpropane tri[poly(propylene glycol), amino-terminated] ether; and the organic solvent is one of DMF, DMSO and toluene.
[0028] Furthermore, the mass ratio of the cross-linking agent to the organic solvent is 1:(180-200), preferably 1:193.
[0029] Furthermore, the molar ratio of the cross-linking agent to polyethylene glycol is 1:(1-4), preferably 1:3.
[0030] Furthermore, in the cross-linking reaction, the heating condition is heating at 60°C-80°C for 1-3h; preferably, heating at 70°C for 2h.
[0031] In some embodiments, the subsequent treatment includes cooling, vacuum degassing, curing, and demolding to obtain a polyurethane urea elastomer containing dynamic covalent bonds.
[0032] Furthermore, the subsequent treatment is specifically as follows: after the reaction is completed, the mixture is cooled to room temperature and vacuum degassing is performed until no bubbles are generated, and then the mixture is placed in an oven at 80° C. for curing for 12 hours. After demolding, a polyurethane urea elastomer containing dynamic covalent bonds is obtained.
[0033] In some embodiments, the lithium salt is selected from one of lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluoromethanesulfonyl)imide, lithium dicyanotriazole, lithium tetrafluoroborate and lithium bis(oxalatoborate); preferably, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide.
[0034] In some embodiments, the plasticizer is selected from one or more of tetraethylene glycol dimethyl ether and succinonitrile; preferably, the plasticizer is tetraethylene glycol dimethyl ether.
[0035] Furthermore, the preparation process of the lithium salt solution is: adding plasticizer to the lithium salt to dissolve, adding dropwise while dissolving, until the lithium salt is completely dissolved, and then adding the remaining plasticizer. The volume fraction of the fluoroethylene carbonate (in the total volume fraction) is 3-8%; preferably, the volume fraction of the fluoroethylene carbonate is 5%.
[0036] The mass ratio of LiTFSI to TEGDME is (1-5):(5-10), preferably (1-2):(6-7), and more preferably 2:7; the optimal ratio is that the concentration of LiTFSI is 1 mol / L.
[0037] In some embodiments, after soaking, the polyurethaneurea elastomer PUU is a cylinder with a diameter of 1.6 cm and a thickness of 0.11-0.13 mm.
[0038] In some embodiments, the soaking time is 1-14 minutes; preferably, the soaking time is 2-5 minutes; more preferably, the soaking time is 4 minutes. The way to control the lithium salt content is to control the soaking time.
[0039] In some embodiments, the entire reaction process should be carried out under nitrogen-filled conditions, and the product of the reaction should be guaranteed to be anhydrous.
[0040] In a third aspect, the present invention provides a battery comprising the quasi-solid polymer electrolyte.
[0041] The present invention relates to a quasi-solid polymer electrolyte and a preparation method thereof. The method comprises preparing a new polyurethane urea type polymer containing dynamic covalent bonds, and on this basis, a post-immersion method is used to set a time gradient to screen out a quasi-solid polymer electrolyte with excellent mechanical properties and ionic conductivity. The polyurethane urea is designed as a mesh structure and is rich in a large number of hydrogen bonds, which gives the electrolyte excellent mechanical properties. The introduction of dynamic covalent bonds gives the quasi-solid electrolyte excellent self-healing properties. Through the post-immersion method and screening, a healable quasi-solid polymer electrolyte with excellent electrical properties and balanced toughness and ionic conductivity is obtained. Fluoroethylene carbonate is added to the immersion solution as a stabilizer for the electrolyte, which further improves the mechanical properties and cyclic stability. The synthesis method of the healable quasi-solid polymer electrolyte with balanced toughness and ionic conductivity proposed by the present invention has the characteristics of simple and quick operation, high synthesis efficiency, controllable process and low cost, and has broad application prospects.
[0042] One or more technical solutions of the present invention have the following beneficial effects:
[0043] 1. Construct a polyurethane urea elastomer containing dynamic covalent bonds, add lithium salt and plasticizer to the polymer by post-immersion method, and add FEC (fluoroethylene carbonate) as an electrolyte stabilizer. By controlling the immersion time, screen out a quasi-solid polymer electrolyte with balanced mechanical properties and ionic conductivity, which also has excellent electrochemical properties and high practical applicability.
[0044] 2. During post-immersion, by adding FEC (fluoroethylene carbonate) as a stabilizer for the electrolyte, the mechanical properties can be improved and the quasi-solid polymer electrolyte can still have good cycle stability at 800h, and the cycle stability voltage is lower.
[0045] 3. The preparation method provided by the present invention has easy-to-obtain raw materials, low synthesis cost, and low requirements on reaction conditions and equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0047] Figure 1 This is a stretched image of the product prepared in Example 1;
[0048] Figure 2 Stretched image of the product prepared in Example 2; FEC was added and soaked for 1 min;
[0049] Figure 3 Stretched image of the product prepared in Example 3; FEC was added and soaked for 4 minutes;
[0050] Figure 4 Stretched image of the product prepared in Example 4; FEC was added and soaked for 7 minutes;
[0051] Figure 5 Stretched image of the product prepared in Example 5; FEC was added and soaked for 14 minutes;
[0052] Figure 6 This is a stretched image of the product prepared in Comparative Example 1;
[0053] Figure 7 Stretched image of the product prepared in Comparative Example 2; no FEC was added, and the mixture was immersed for 4 minutes;
[0054] Figure 8 The product prepared in Example 3 was -2 The charge / discharge curve of lithium symmetric battery under current density;
[0055] Fig. 9 The product prepared in Comparative Example 1 was -2 The charge / discharge curve of lithium symmetric battery under current density;
[0056] Fig.10 The product prepared in Comparative Example 2 was -2 The charge / discharge curve of lithium symmetric battery under current density;
[0057] Fig.11 These are optical microscope images of the product prepared in Example 3 before and after self-repair; wherein a is before repair and b is after repair. DETAILED DESCRIPTION
[0058] Explanation of terms involved:
[0059] SPEs: solid polymer electrolytes.
[0060] PUU: polyurethane urea.
[0061] PEG (Mn = 2000): polyethylene glycol with a mass fraction of 2000, used as a reaction substrate, with the following structural formula:
[0062] PEO: Polyethylene oxide.
[0063] CH3CN: acetonitrile.
[0064] HDI: Hexamethylene diisocyanate, an indispensable part of the polyurethane synthesis process, has the following structural formula:
[0065] ADF: 4,4'-diaminodiphenyl disulfide, used as a chain extender, the structural formula is as follows:
[0066]
[0067] T-403: Trimethylolpropane tri[poly(propylene glycol), amino terminated] ether, used as a crosslinking agent, with the following structure:
[0068]
[0069] TEGDME: Tetraethylene glycol dimethyl ether, used as a plasticizer, the structural formula is as follows:
[0070]
[0071] LiTFSI: Lithium bis(trifluoromethanesulfonyl)imide, used as part of the battery electrolyte, has the following structural formula:
[0072] DMF: N,N-dimethylformamide, used as a solvent for the reactants, with the following structural formula:
[0073]
[0074] DBTDL: dibutyltin dilaurate, used as a catalyst for the reaction.
[0075] FEC: Fluoroethylene carbonate, used as a reaction stabilizer.
[0076] Room temperature: has a well-known meaning in the technical field, generally refers to 25±2°C.
[0077] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0078] Example 1
[0079] Preparation of polyurethane urea elastomer PUU containing dynamic covalent bonds:
[0080] First, add 2 g of 2000 g·mol -1 PEG was heated at 60℃ in a heating mantle for more than 20 minutes under magnetic stirring until PEG was completely melted. Then 0.3364g HDI was added to a 15mL reagent tube, and 10ml DMF and 20μL DBTDL were added at the same time, and vortexed for 5min. The fully dissolved reagents were added to the above 100mL round-bottom flask, and heated at 70℃ in a heating mantle for 1.5h under magnetic stirring.
[0081] Take a 10 mL reagent tube, add 0.124 g ADF and 5 mL DMF into the tube, sonicate until ADF is completely dissolved, add to the above 100 mL round-bottom flask, and heat at 70°C in a heating mantle for 2 h under magnetic stirring.
[0082] Take a 10mL reagent tube, add 0.1467g T-403 and 10mL DMF, vortex for 5min, add the fully dissolved reagent to the above 100mL round-bottom flask, and heat at 70℃ in a heating mantle for 2h under magnetic stirring. After the reaction is completed, cool to room temperature, pour into a silicone mold, vacuum degassing, degassing until no bubbles are generated, place in an 80℃ oven for curing for 12h, and after demolding, the target polyurethane urea elastomer PUU containing dynamic covalent bonds is obtained.
[0083] Example 2
[0084] The polyurethane urea elastomer PUU containing dynamic covalent bonds obtained in Example 1 was machined, and the thickness range was selected to be 0.11-0.13 mm. The polyurethane urea elastomer was pressed into a sheet to prepare a disc with a diameter of 1.6 cm.
[0085] Take a 10mL reagent tube, add 2g LiTFSI and TEGDME solution (mass ratio 2:7) to it, add dropwise while dissolving until LiTFSI is completely dissolved, and then add TEGDME solution to 7mL. Pour the prepared lithium salt solution into a 10mL small beaker, and add 5% by volume FEC as an electrolyte stabilizer.
[0086] The prepared polyurethane urea elastomer PUU disc was completely immersed in the solution at room temperature and in an argon environment for 1 min. After being taken out, the surface was wiped to obtain a quasi-solid polymer electrolyte A.
[0087] Example 3
[0088] The difference from Example 2 is that the immersion time is 4 minutes. After taking out, the surface is wiped to obtain a quasi-solid polymer electrolyte B.
[0089] Example 4
[0090] The difference from Example 2 is that the immersion time is 7 minutes. After taking out, the surface is wiped to obtain a quasi-solid polymer electrolyte C.
[0091] Embodiment 5:
[0092] The difference from Example 2 is that the immersion time is 14 minutes. After taking out, the surface is wiped to obtain a quasi-solid polymer electrolyte C.
[0093] Comparative Example 1: Preparation of PEOE polymer elastomer electrolyte
[0094] Take the mass fraction as 600000 g·mol -1 6.4g of PEO particles and 2.6g of LiTFSI, keeping the molar ratio of the ethoxy units of PEO and LiTFSI at 16:1, mix them together and add them to a 150mL round-bottom flask, and stir them thoroughly with magnetic stirring. Take 60mL of CH3CN and add it to the round-bottom flask and stir it thoroughly for about 8h. After PEO and LiTFSI are completely mixed and dissolved, pour the mixture into a Teflon mold, flatten it completely, and put it in a vacuum box for degassing until the bubbles are completely removed. After taking it out, put it in an oven and vacuum dry it at 80℃ for 12h to obtain a PEO / LiTFSI film.
[0095] The obtained PEO / LiTFSI membrane is machined, and a portion with a thickness of about 0.13 mm is selected to press the PEO / LiTFSI membrane into a disc with a diameter of 1.6 cm. Take a 10 mL reagent tube, add 2 g of LiTFSI and TEGDME solution to it, and add it dropwise while dissolving until LiTFSI is completely dissolved, and then add TEGDME solution to 7 mL. Pour the configured lithium salt solution into a 10 mL small beaker, and completely immerse the prepared PEO / LiTFSI disc into the solution for 6 hours. After taking it out, wipe the surface to obtain a PEOE polymer elastomer electrolyte.
[0096] Comparative Example 2:
[0097] Different from Example 3, during the soaking treatment, no fluoroethylene carbonate was added to the soaking solution as a stabilizer.
[0098] Figure 1 The tensile curve of the polyurethane urea elastomer PUU containing dynamic covalent bonds prepared in Example 1 is used as the substrate for the subsequent preparation of quasi-solid polymer electrolytes.
[0099] Figure 2, 3 , 4, and 5 are tensile curves of the products prepared in Examples 2, 3, 4, and 5. The post-immersion method is used to make the contents of TEGDME and LiTFSI in the prepared products increase in a gradient. As the immersion time increases, the mechanical properties become worse. Although the mechanical properties are better than those of the immersion for 4 minutes when immersed for 1 minute, the ionic conductivity is poor. The best immersion time of the present invention is 4 minutes, which achieves a balance between mechanical properties and ionic conductivity.
[0100] Depend on Figure 3 It can be seen that in Example 3, which was immersed for 4 minutes, the tensile strain of the quasi-solid polymer electrolyte prepared therein can reach 1200% and the stress is 2.43 MPa.
[0101] Depend on Figure 6 It can be seen that the tensile strain of the PEOE polymer elastomer electrolyte prepared in Comparative Example 1 can reach 460% and the stress is 0.9 MPa. Compared with Comparative Example 1, the quasi-solid polymer electrolyte prepared in Example 3 significantly improves the tensile strength of the material.
[0102] Compared with comparative example 2 (without FEC addition), Figure 7 The quasi-solid polymer electrolyte prepared in Example 3 with the addition of FEC significantly improves the tensile strength of the material. The cyclic stabilizer FEC can improve the uniformity of the quasi-solid polymer electrolyte and reduce the difference in mechanical properties caused by material inhomogeneity; uniform material properties help the material to exhibit better mechanical properties when subjected to external forces.
[0103] Figure 8 , 9 , 10 are the products prepared in Example 3, Comparative Example 1 and Comparative Example 2 at 0.05 mA cm -2 From the charge / discharge curve of lithium symmetric battery under current density, it can be seen that the potential of the product in comparative example 1 rises rapidly and continuously, the voltage of comparative example 2 without adding FEC is high and unstable, and the potential of the sample prepared in example 3 is basically unchanged during the 800h charge and discharge process and is very stable. Compared with comparative example 1, the quasi-solid polymer electrolyte prepared in example 3 significantly improves the stability of battery cycle; and compared with comparative example 2, the voltage is lower and more stable after adding FEC.
[0104] Fig.11 The images are of the scratch repair and self-healing of the product prepared in Example 3 before and after. The obvious repair effect can be seen in the figure, and the scratch almost disappears. The quasi-solid polymer electrolyte prepared in Example 3 has excellent self-healing performance.
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A quasi-solid polymer electrolyte, characterized in that: include: A polyurethane urea elastomer and a soaking solution; the soaking solution comprises a lithium salt, a plasticizer and fluoroethylene carbonate.
2. The quasi-solid polymer electrolyte according to claim 1, characterized in that: The lithium salt is selected from one of lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluoromethanesulfonyl)imide, lithium dicyanotriazole, lithium tetrafluoroborate and lithium bis(oxalatoborate); preferably, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide; The plasticizer is selected from tetraethylene glycol dimethyl ether and succinonitrile; preferably, the plasticizer is tetraethylene glycol dimethyl ether; The volume fraction of the fluoroethylene carbonate is 3-8%; preferably, the volume fraction of the fluoroethylene carbonate is 5%; The mass ratio of lithium salt to plasticizer is (1-5):(5-10), preferably (1-2):(6-7).
3. The method for preparing a quasi-solid polymer electrolyte according to claim 1 or 2, characterized in that: include: preparing a polyurethane urea elastomer containing dynamic covalent bonds and processing it into a polyurethane urea elastomer tablet; The plasticizer and the lithium salt are mixed to prepare a lithium salt solution, and fluoroethylene carbonate is added thereto to obtain a soaking solution; The polyurethane urea elastomer pressed sheet is completely immersed in the soaking solution to obtain a quasi-solid polymer electrolyte.
4. The method for preparing a quasi-solid polymer electrolyte according to claim 3, characterized in that: The preparation method of the polyurethane urea elastomer comprises the following steps: adding a mixed solution of an organic solvent, dibutyltin dilaurate and hexamethylene diisocyanate to completely melted polyethylene glycol for heating, then sequentially adding a chain extender solution for prepolymerization, adding a crosslinker solution for crosslinking, and finally performing subsequent treatment to obtain a polyurethane urea elastomer containing dynamic covalent bonds.
5. The method for preparing a quasi-solid polymer electrolyte according to claim 4, characterized in that: In the mixed solution, the ratio of hexamethylene diisocyanate, organic solvent and dibutyltin dilaurate is (0.2-0.4):(5-15):(15-25), g:mL:μL; the organic solvent is DMF or DMSO; Further, the mixture is added to completely melted polyethylene glycol and heated at 60°C-80°C for 1-2h; Furthermore, the chain extender solution includes a chain extender and an organic solvent for dissolving the chain extender; the chain extender is 4,4'-diaminodiphenyl disulfide; the organic solvent is one of DMF and DMSO; Further, the ratio of the chain extender to the organic solvent is 1:(200-240); the molar ratio of the chain extender to the polyethylene glycol is 1:(1-4); Furthermore, in the prepolymerization reaction, the heating condition is heating at 60°C-80°C for 1-3h; Further, the crosslinking agent solution comprises a crosslinking agent and an organic solvent for dissolving the crosslinking agent; the crosslinking agent is trimethylolpropane tri[poly(propylene glycol), amino-terminated] ether; the organic solvent is one of DMF, DMSO and toluene; Furthermore, the mass ratio of the cross-linking agent to the organic solvent is 1:(180-200); the molar ratio of the cross-linking agent to the polyethylene glycol is 1:(1-4); Furthermore, in the cross-linking reaction, the heating condition is heating at 60°C-80°C for 1-3h.
6. The method for preparing a quasi-solid polymer electrolyte according to claim 4, characterized in that: The subsequent treatment includes cooling, vacuum degassing, curing, and demoulding to obtain a polyurethane urea elastomer containing dynamic covalent bonds.
7. The method for preparing a quasi-solid polymer electrolyte according to claim 3, characterized in that: The lithium salt is selected from the group consisting of lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluoromethanesulfonyl)imide, lithium dicyanotriazole, lithium tetrafluoroborate and lithium bis(oxalatoborate); preferably, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide; The plasticizer is selected from one of tetraethylene glycol dimethyl ether and succinonitrile; preferably, the plasticizer is tetraethylene glycol dimethyl ether.
8. The method for preparing a quasi-solid polymer electrolyte according to claim 3, characterized in that: The preparation process of the lithium salt solution is as follows: adding a plasticizer to the lithium salt to dissolve it, adding dropwise while dissolving until the lithium salt is completely dissolved, and then adding the remaining plasticizer; Furthermore, the mass fraction of the fluoroethylene carbonate is 3-8%; Furthermore, the mass ratio of the lithium salt to the plasticizer is (1-5):(5-10), preferably (1-2):(6-7).
9. The method for preparing a quasi-solid polymer electrolyte according to claim 3, characterized in that: When the polyurethane urea elastomer pressed sheet is completely immersed in the soaking solution, the soaking time is 1-14 minutes; preferably, the soaking time is 2-5 minutes.
10. A battery comprising the quasi-solid polymer electrolyte according to claim 1 or 2.
Citation Information
Cited By
Solid polymer electrolyte, preparation method thereof, battery and electric device
CN121726521A
